Don't go to sleep - Moore, Bryce (Naperville, Illinois : Sourcebooks Fire, 2022)
In 1918 New Orleans, seventeen-year-old Gianna Crutti's worries about her family's grocery, the Great War, and influenza are overshadowed when a murderer returns to terrorize the city--years after he attacked Gianna's parents and left her with a psychic connection between them.
Ages 14-18.
Grades 10-12.
Keywords: Serial murderers -- Fiction; Italian Americans -- Fiction; Influenza Pandemic, 1918-1919 -- Fiction; Occultism -- Fiction; Mystery and detective stories; New Orleans (La.) -- History -- 20th century -- Fiction; Thrillers (Fiction); Paranormal fiction; Detective and mystery fiction; Novels